SPORT MANAGEMENT: SPORT MANAGEMENT - Khudayberdieva Dilafruz Abidovna; Abbasov Bakhadir Asatillaevich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article contains theoretical considerations about the development of management in sports, the lack of highly qualified and experienced specialists in physical culture, the development and expansion of sports sections and directions, as well as the functions and principles of sports management.